Pengelolaan Persediaan Barang Habis Pakai (BHP) di Perguruan Tinggi: Studi Kasus di Politeknik Negeri Bengkalis - Ningsih, Sri Septia; Nurhazana, Nurhazana (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2024)
State Polytechnic of Bengkalis is a Vocational Higher Education Institution. Inventory refers to assets in the form of goods or supplies intended to support operational activities. This research aims to examine the management of consumable inventory within the Higher Education environment, focusing on State Polytechnic of Bengkalis as a case study. Consumable inventory plays a crucial role in supporting the operations of the Higher Education institution, encompassing all types of materials, equipment, and resources used in daily activities. This study employs a qualitative descriptive research method, involving in-depth interviews with three informants at the State Polytechnic of Bengkalis. The research findings reveal several important aspects. First, the types of consumable inventory used by the State Polytechnic of Bengkalis include consumables, maintenance materials, spare parts, raw materials, and other supplies. Second, the implementation of RI Government Regulation No. 27 of 2014 in the management of consumable inventory at the State Polytechnic of Bengkalis has not been fully realized. The management of consumable inventory at the State Polytechnic of Bengkalis includes needs planning and budgeting, procurement, usage, security and maintenance, administration, evaluation, coaching, supervision, and control. However, there are still shortcomings, such as delays in submitting inventory needs documents by each department, which results in suboptimal planning. Additionally, the absence of standardized Standard Operating Procedures (SOP) causes inconsistencies in the management of consumable inventory at the State Polytechnic of Bengkalis. Despite the lack of standardized SOP, the State Polytechnic of Bengkalis continues to ensure that the procedures used in managing consumable inventory comply with recommended standards.